Applying Strategic Change Cycle to Stunting Reduction: A Case Study from Tana Tidung Regency Indonesia - Silva Tika Hindarfergia; Wike; Farida Nurani (The Journal of Indonesia Sustainable Development Planning, 2025)
Tana Tidung Regency experienced an unusual stunting trend, rising from 22.8 percent (2021) to 30.7 percent (2022), then dropping sharply to 15.1 percent (2023), the fastest decline in North Kalimantan. This study analyzes the strategic planning process of the Health Office using the Strategy Change Cycle model. A qualitative approach was employed, utilizing purposive sampling and interactive model data analysis, with data sourced from informants, documents, and activities. The results show that the significant achievement was driven by leadership commitment, cross-sector collaboration, and local innovations. However, challenges remain, including weak integration of stunting issues into strategic documents, limited resources, and the absence of clear performance indicators and a dedicated Regional Action Plan. The study concludes that adaptive strategies tailored to local contexts can effectively accelerate stunting reduction, even in resource-constrained areas. These findings contribute to the literature on strategic planning in local governments and support the achievement of SDG 2 and SDG 3.